2022
DOI: 10.1097/bot.0000000000002330
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Malunion After All-Arthroscopic Coracoclavicular Stabilization for Displaced and Unstable Lateral Clavicle Fractures

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…However, our study adds to these findings, because in their study only 30 out of 122 (25%) patients were available for follow-up analysis compared to 353 out of 619 (response rate 57%) patients with mean follow-up of 7.4 (SD 2.9) years in our study [22]. Different operative techniques have been described for the stabilization of displaced lateral clavicle fractures, each with their pros and cons [23][24][25][26][27][28][29]. A recent systematic review, comparing different operative treatment strategies in patients with displaced lateral clavicle fractures, found that plate fixation was associated with the highest postoperative function scores and lowest risk of complications, followed by coracoclavicular fixation [8].…”
Section: Patient-reported Outcomesmentioning
confidence: 74%
See 2 more Smart Citations
“…However, our study adds to these findings, because in their study only 30 out of 122 (25%) patients were available for follow-up analysis compared to 353 out of 619 (response rate 57%) patients with mean follow-up of 7.4 (SD 2.9) years in our study [22]. Different operative techniques have been described for the stabilization of displaced lateral clavicle fractures, each with their pros and cons [23][24][25][26][27][28][29]. A recent systematic review, comparing different operative treatment strategies in patients with displaced lateral clavicle fractures, found that plate fixation was associated with the highest postoperative function scores and lowest risk of complications, followed by coracoclavicular fixation [8].…”
Section: Patient-reported Outcomesmentioning
confidence: 74%
“…Different operative techniques have been described for the stabilization of displaced lateral clavicle fractures, each with their pros and cons [ 23 29 ]. A recent systematic review, comparing different operative treatment strategies in patients with displaced lateral clavicle fractures, found that plate fixation was associated with the highest postoperative function scores and lowest risk of complications, followed by coracoclavicular fixation [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation